2019
DOI: 10.1021/acs.jmedchem.8b01766
|View full text |Cite
|
Sign up to set email alerts
|

2-Aminothiazole Derivatives as Selective Allosteric Modulators of the Protein Kinase CK2. 1. Identification of an Allosteric Binding Site

Abstract: CK2 is a ubiquitous Ser/Thr protein kinase involved in the control of various signaling pathways and is known to be constitutively active. In the present study, we identified aryl 2-aminothiazoles as a novel class of CK2 inhibitors, which displayed a non-ATP-competitive mode of action and stabilized an inactive conformation of CK2 in solution. Enzyme kinetics studies, STD NMR, circular dichroism spectroscopy, and native mass spectrometry experiments demonstrated that the compounds bind in an allosteric pocket … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
82
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(86 citation statements)
references
References 41 publications
4
82
0
Order By: Relevance
“…The preliminary Structure-Activity Relationships (SAR) obtained from a small series of analogs of the original hit compound 1 (Figure 1) had suggested that the three aryl ring system as well as the carboxylic acid function are needed for CK2α inhibition. 20 In order to gain further insight into essential key features and to optimize the inhibitory potency, we synthesized a targeted set of derivatives to systematically explore the SAR around the new scaffold. First, we varied the position and number of the essential carboxyl function (compounds 9 and 30, Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The preliminary Structure-Activity Relationships (SAR) obtained from a small series of analogs of the original hit compound 1 (Figure 1) had suggested that the three aryl ring system as well as the carboxylic acid function are needed for CK2α inhibition. 20 In order to gain further insight into essential key features and to optimize the inhibitory potency, we synthesized a targeted set of derivatives to systematically explore the SAR around the new scaffold. First, we varied the position and number of the essential carboxyl function (compounds 9 and 30, Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1). 20 We also synthesized and tested the pyridinyl derivative 17 in order to explore more polar heterocycles with a ring dipole moment similar to the nitrophenyl compound. However, the measured IC 50 value of 19 µM was unfavorable, suggesting that the polar H-bond acceptor nitrogen in the ring is not complementary to the electrostatic potential of the binding pocket.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Acylthiourea and aminothiazole are the bioisosteres in accordance with conceptual cyclization principle. Moreover, aminothiazole is a well‐known pharmacophore with diverse biological properties, for instance, neuroprotection, anti‐inflammation, antibacterial and anticancer . We envision that aminothiazole as linker in our target compounds will enhance their selectivity and affinity with Hh‐related receptors.…”
Section: Introductionmentioning
confidence: 99%